Extreme Violation of Sanctity of Medical Institutes & Dumb, Deaf, Blind & Dead Medical Community! - Haque, Anwar Ul (International Journal of Pathology, 2018)
In last 29 days the world has witnessed unprecedentedviolation of sanctity of Medical Institutionsby Israel in Gaza! Several hundred innocentchildren and as much unarmed civilian womenwere brutally killed by unmanned drones, distanttank attacks and fire from ships! Daylight murdersand massacres were carried out without anyregret and shame! Their arrogance, racism andstiff necks can be seen and felt! No shame, no regret,no remorse! The killers and murderers displayedremarkable cowardice! They didn’t dareto come in close contacts with armed defensivepersonnel! The citizens of Gaza had no aerial protectionlike iron dome of Israel; neither they hadAir Force, navy, or proper military! The entiresaga was one sided! The pretext that 3 Israeliswere murdered by Hamas turned out to be false;confirming that all this was per planned for theMuslim holy month of Ramadan and partly duringWorld Football Match! It’s interesting thatIsrael has right of self-defence but not the Gazansand Palestinians in general!